Optimization of grouper (Epinephelus coioides) seed density in a recirculating system for growth, survival rate, and feed efficiency - Agus Putra AS; Muslimatus Sakdiah; Pebry Aisyah Putri Batubara; Adnan Achmad (Jurnal Perikanan Terpadu, 2026)
Recirculating Aquaculture Systems (RAS) are an important innovation in the development of sustainable aquaculture, enabling the management of high stocking densities in controlled environments. This study aimed to evaluate the effect of different stocking densities of grouper (Epinephelus coioides) seedlings on growth performance, feed efficiency, survival rate, and water quality in a RAS. In this study, grouper juveniles (9.4 ± 0.54 cm and 14.22 ± 0.67 g) were reared in 100-liter aquaria and cultured for 70 days. The experiment was arranged in a Completely Randomized Design (CRD) with three stocking density treatments (15, 20, and 25 fish/aquarium), each with three replicates. Observed parameters included total length, total weight, Weight Gain (WG), Specific Growth Rate (SGR), condition factor (K), Feed Intake (FI), Feed Conversion Ratio (FCR), Feed Efficiency Ratio (FER), water quality (salinity, dissolved oxygen, temperature, pH), and Survival Rate. The results showed that increasing the stocking density up to 25% produced the best growth performance and feed efficiency (WG 574%, SGR 2.72%/day, FCR 1.32, FER 0.76) without reducing the survival rate (SR 100%). Water quality remained within optimal ranges, although slight decreases in dissolved oxygen and pH were observed. Therefore, the RAS was proven to effectively and sustainably support high-density grouper aquaculture.